High-intensity interval training induces lactylation of fatty acid synthase to inhibit lipid synthesis - Xuefei Chen; Wenhua Huang; Jingbo Zhang; Yanjun Li; Zheng Xing; Lanlan Guo; Hongfeng Jiang; Jing Zhang (2023)
The aim of study was to observe the effect of increased lactate levels during high-intensity interval training (HIIT) on protein lactylation, identify the target protein, and investigate the regulatory effect of lactylation on the function of the protein.C57B/L6 mice were divided into 3 groups: the control group, HIIT group, and dichloroacetate injection + HIIT group (DCA + HIIT). The HIIT and DCA + HIIT groups underwent 8 weeks of HIIT treatment, and the DCA + HIIT group was injected DCA before HIIT treatment. The expression of lipid metabolism-related genes was determined. Protein lactylation in subcutaneous adipose tissue was identified and analyzed using 4D label-free lactylation quantitative proteomics and bioinformatics analyses. The fatty acid synthase (FASN) lactylation and activity was determined.HIIT had a significant effect on fat loss; this effect was weakened when lactate production was inhibited. HIIT significantly upregulated the protein lactylation while lactate inhibition downregulated in iWAT. FASN had the most modification sites. Lactate treatment increased FASN lactylation levels, inhibited FASN activity, and reduced palmitate and triglyceride synthesis in 3T3-L1 cells.This investigation revealed that lactate produced by HIIT increased protein pan-lactylation levels in iWAT. FASN lactylation inhibited de novo lipogenesis, which may be an important mechanism in HIIT-induced fat loss.